Catch Catwoman! - Wrecks, Billy; De Carlo, Mike; Doescher, Erik; Tanguay, Dave (New York Random House, 2013)
When Catwoman steals their stuff, it's up to Batman and the Super Friends to catch the criminal
"A comic reader."
At head of title: DC Super Friends
2
Keywords: Catwoman -- (Fictitious character) -- Juvenile fiction; Catwoman (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction